Циркулярна економіка як частина корпоративної стратегії організації - Злотнік, М. Л.; Zlotnik, M. L. (Видавництво Львівської політехніки, 2021)
Досліджено впровадження концепції циркулярної економіки в корпоративну стратегію організації. Проаналізовано різні підходи авторів до визначення поняття циркулярної економіки, корпоративної стратегії та бізнес-моделей, проілюстровано процес стратегічного планування з урахуванням концепції циркулярної економіки, ідентифіковано бізнес-моделі циркулярної економіки та їх взаємозв’язок зі стратегією організації. Проаналізовано впровадження циркулярної економіки у корпоративну стратегію на прикладі вибраних підприємств та сформовано висновки.

In today’s environment, organizations need new corporate strategies and models to protect profitability and competitiveness, as well as the heritage of natural resources. A circular economy is a model of production and consumption in which all resources and products are reused in the economic cycle, which can significantly reduce waste generation and create additional economic benefits for business. This is especially important in the context of the recovery from the economic crisis caused by the COVID-19 pandemic. Implemented quarantine restrictions have revealed how sensitive to global risks and inflexible the linear economic system is. The purpose of this study is to identify and analyze ways to implement circular economy models in the corporate strategy of the organization. The objectives of the article are to study the latest publications on the definition of circular economy, corporate strategy and their relationship, description of the strategic planning process taking into account the models of circular economy, identification of basic business models of circular economy, analysis of examples of implementation of circular models conclusions. To achieve the goal of the study, the authors' different approaches to the interpretation of the concept of “corporate strategy” and its formation within the circular economy were analyzed, the process of strategic planning was highlighted and the main types of values created by the circular economy were identified. The key circular business models and their relationship with the corporate strategy of the organization are highlighted. The main part of the article analyzes examples of implementation of the concept of circular economy in the corporate strategies of four selected Italian companies in various industries. A comparative description of the roles of the circular economy in the corporate strategy of each company and the benefits gained in the process of its implementation was carried out. Conclusions were drawn on the importance of implementing the ideas of the circular economy at the stage of forming the strategy of the enterprise to achieve economic, environmental and social benefits.
Circular economy as a part of the organizational corporate strategy
Keywords: циркулярна економіка; корпоративна стратегія; стратегічне планування; сталий розвиток; бізнес-модель; створення цінності; відновлення ресурсів; circular economy; corporate strategy; strategic planning; sustainable development; business model; value creation; resource recovery; 65.011.12